Analisis Pengaruh pH terhadap Stabilitas Reologi dan Kinerja Emulsi pada Sistem Alkali-Polymer (Xanthan Gum-NaOh) untuk Aplikasi Enhanced Oil Recovery - E endri Bima Octoberry; Rusandy Ramadhan; Tirza Rofionha Edelweis Pesiwarissa (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Alkali–polymer systems in Enhanced Oil Recovery (EOR) improve oil displacement efficiency through mobility control and interfacial tension reduction. This study analyzes the effect of pH variation on rheological stability and emulsion performance of a xanthan gum–NaOH alkali–polymer system. Laboratory tests were conducted using brine with 10,000 ppm salinity at pH 9, 10, 11, and 12 under temperatures of 25 °C and 90 °C. The evaluated parameters included 24-hour solution compatibility, viscosity, and emulsion formation using light oil. The results showed that the system was compatible at pH 9–11, while instability occurred at pH 12. Viscosity increased from 2.11 cP at pH 9 to 2.13 cP at pH 10, then decreased to 2.01 cP at pH 11. Significant emulsion formation began at pH 11, producing a weak Winsor III middle phase.